Pelatihan TikTok Affiliate Untuk Peningkatan Pendapatan Karang Taruna Rusunawa Putri Cempo Surakarta - Aminah, Siti; Hasmarani, Hesti; Abidin, Ali Zainal (JURNAL PENGABDIAN MANAJEMEN, 2024)
Based on the situation analysis, it is known that 92.6% of youth in the Putri Cempo Rusunawa area, Surakarta City, Central Java Province do not know about the TikTok Affiliate program. This service uses a method of providing training to youth organizations. The purpose of this program is to help youth organizations increase their knowledge and skills to generate additional income online through the TikTok platform by providing training on the use of TikTok Affiliate. TikTok Affiliate is a program officially issued by the TikTok application. Stages of community service activities: (1) Introduction to the TikTok platform and TikTok Shop Affiliate; (2) Training to teenagers and practice of creating TikTok Shop Affiliate accounts and (3) Providing tips and tricks for creating attractive promotional content and (4) Providing strategies for increasing income on TikTok by selling products. The results of this training activity are increased knowledge about TikTok and TikTok Affiliate, teenagers are able to create TikTok Shop accounts and have the desire to become content creators. TikTok Affiliate training for youths of Rusunawa Putri Cempo successfully increased the knowledge and skills of teenagers in utilizing the TikTok application to generate income online, this training is expected to help youths increase their income and improve their quality of life through the TikTok Affiliate program.